Pathogenic mechanisms in murine autoimmune thyroiditis: short- and long-term effects of in vivo depletion of CD4+ and CD8+ cells. - Kong, Y; Waldmann, H; Cobbold, S; Giraldo, A; Fuller, B; Simon, L (1989)
Both murine CD4+ and CD8+ cells are found in the thyroid infiltrate in experimental autoimmune thyroiditis (EAT) induced with mouse thyroglobulin (MTg). MTg activation of immune cells in vitro enables CD4+ cells to transfer thyroiditis adoptively and to aid the cytotoxic capacity of CD8+ cells for thyroid monolayers. To dissect their relative contribution to pathogenesis in vivo, depleting doses of paired rat monoclonal antibodies (MoAb) recognizing two distinct CD4 or CD8 epitopes were injected alone or in combination. Early treatment with CD4 MoAb interfered with the induction and development of EAT, whereas similar treatment with CD8 MoAb reduced infiltration moderately and did not enhance antibody response. To examine the long-term effect of therapy on advancing EAT, administration of MoAb was delayed to days 21 and 25, and thyroids were analysed immunohistochemically on days 28 and 70. Whereas control mice showed about 30% CD4+ and CD8+ cells at a 2:1 ratio (the remainder being mostly macrophages) on both days 28 and 70, the CD4 therapy regime led to reduced severity and the lesions on day 70 contained very low percentage of CD4+ cells, but elevated percentage of CD8+ cells (ratio 1:3.5). The CD8 therapy regime led to reduced CD8+ cells without changing the range of CD4+ cells (ratio 4:1). Thus, subset involvement may be influenced by the MoAb used. When CD4 and CD8 MoAb were combined, greater than 50% of the thyroids were cleared of all inflammatory cells; lesions when found were very small and contained less than 10% T cells (ratio 1:1). Since emerging T cells were not retained in the thyroid despite ongoing antigenic stimulus leading to increased antibody titres, the therapeutic effect of MoAb, even at an advanced stage of disease, was long lasting.